The highly relativistic surfatron acceleration of electrons by electromagnetic wave packet in space plasma - Erokhin, N.S.; Zolnikova, N.N.; Shkevov, R.; Mikhailovskaya, L.A. (Вопросы атомной науки и техники, 2015)
On the basis of numerical calculations it is considered the highly relativistic surfatron acceleration of electrons in space plasma by spatially localized electromagnetic wave packet for the large initial energy of particles. The optimum conditions for strong electrons acceleration are formulated. The estimate of accelerated electrons maximum energy is given.